Center and periphery
1 online resource (332 pages)
Keywords: William Chester Jordan’s scholarship has demonstrated the complexity of negotiating power at both the center and margins of medieval society, taking us into the inner chambers of medieval power structures where kings, churchmen and courtiers dwell to the margins of society inhabited by disenfranchised peoples such as Jews, women and the poor. Center and Periphery: Studies on Power in the Medieval World in Honor of William Chester Jordan , edited by Katherine L. Jansen, G. Geltner and Anne E. Lester, honors Professor Jordan by taking up these themes and expanding them from France into Spain, Italy, the Lowlands, and the Mediterranean. The volume highlights how Jordan’s work inspired and influenced a generation of medievalists working in North America and Europe today. Contributors are John W. Baldwin, Adam J. Davis, Jonathan Elukin, Hussein Fancy, Michelle Garceau, G. Geltner, Erica Gilles, Holly J. Grieco, Maya Soifer Irish, Katherine L. Jansen, Emily Kadens, Richard Landes, Jacques Le Goff, Anne E. Lester, Christopher MacEvitt, David Nirenberg, Mark Gregory Pegg , Jarbel Rodriguez, E.M. Rose and Teofilo Ruiz.